Longitudinal associations between coach-athlete relationship quality and individual injury rate among young handball players: A variable and person-centered approach in intensive training centers - Roux, V.; Trouilloud, D. (International Journal of Sports Science & Coaching, 2025)
This study explores the potential associations between the evolution of coach-athlete relationship quality (in terms of closeness, commitment, and complementarity) and the athletes` individual injury rate over a sport season. 203 young French handball players (Mage = 15.38, 47.3% women) involved in intensive training centers completed a French version of the Coach-Athlete Relationship Questionnaire at the beginning, middle, and end of the season. The athlete follow-up allowed their individual injury rate over the season to be captured. Both variable and person-centered approaches were used to explore the temporal associations between these variables. A linear growth model and a multiple regression analysis indicated that the evolution of coach-athlete relationship quality was negatively related to athletes` individual injury rate over the season. In addition, latent class growth analyses and ANOVA revealed inter-individual differences in the evolution of this association, indicating that athletes who perceived a deterioration in the relationship with their coach were more often injured during the season. This study is the first to highlight a temporal association between coach-athlete relationship quality and athletes` individual injury rate over time, and thus provides stimulating perspectives for future research.